Review of Driving Waveform for Electrowetting Displays - Yi, Zichuan; Zhang, Hu; Zeng, Wenjun; Feng, Haoqiang; Long, Zhengxing; Liu, Liming; Hu, Yunfeng; Zhou, Xichen; Zhang, Chongfu (Frontiers in Physics, 2021)
Electrowetting display (EWD) is the most potential technology among new electronic paper technologies. It not only has the advantages of electrophoretic display (EPD) technology but also can realize color video playback. Therefore, this technology has been widely studied in recent years. Driving waveform is a voltage sequence which can drive pixels to display gray scales in EWDs. As one of the key technologies, it directly affects the display effect of pixels. In this paper, we give a review of the display principle of EWDs and the research status of driving waveforms. At the same time, the contact angle hysteresis, charge trapping, and oil splitting are also reviewed, which can provide a reference value for designing driving waveforms.